Identification of highly gifted adolescents methods and experiences - Trost, Gunter T.
This papaer is a multi-stage program for the identification of highly gifted students is presented which was run by German National Scholarship Foundation. First the organization and its function will be introduced. Then the assessment program will be described, and some of the results of the evaluation of this program will be discussed. The paper will close in four theses on principles and methods of identifying the highly gifted.
Keywords: German National Scholarship Foundation; Gifted children -- Identification; Gifted children -- Education; Academic achievement